Effects of a thermoplastic foot orthosis on patellofemoral pain in a collegiate athlete: A single-subject design - Way, M. C. (Journal of Orthopaedic & Sports Physical Therapy, 1999)
Abstract: Study Design: Single-subject, A-B-A-B format. Objective: To evaluate the effects of a foot orthosis on pain and function by controlling forefoot pronation. Background: Foot orthoses have been recommended to treat patellofemoral pain by controlling excessive pronation, but few studies have used an experimental design to validate this approach. Methods and Measures: A 19-year-old collegiate softball player had an acute onset of patellofemoral pain in her left knee. A visual analog scale was used to assess pain intensity and a functional index questionnaire (FIQ) was used to measure the subject`s perceived functional level. Results: Statistical analysis using the celeration line technique showed significant improvements between all the consecutive baseline and intervention phases of the VAS data and in 7 of the 9 paired phases of the FIQ data. Conclusions: Limiting pronation with a thermoplastic orthosis was an effective treatment for this subject.